Analisis Mutu Pendidikan Islam (Input, Proses & Output) (Studi di MI Unggulan Ash-Shiddiqiyyah-3 Purworejo) - Syaefudin Syaefudin (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2020)
The purpose of this study is to analyze the quality of Islamic education which includes: input, process, output. Specifically on the object of study in this study, namely in SD/MI Unggulan Ash-Shiddiqiyyah-3 di Purworejo. This type of research is qualitative. Using an educational sociology approach. Data collection was obtained directly from informants through interviews, observations, and documentation. Data analysis techniques used are data reduction, data display, data verification, and affirmation of conclusions. An important finding in this study is that SD/MI Unggulan Ash-Shiddiqiyyah-3 di Purworejo cannot be said to be a quality school. Because, the three components of education quality have not been fulfilled, namely: overall input, process, and output.The purpose of this study is to analyze the quality of Islamic education which includes: input, process, output.Specifically on the object of study in this study, namely in SD/MI Unggulan Ash-Shiddiqiyyah-3 di Purworejo.This type of research is qualitative. Using an educational sociology approach. Data collection was obtaineddirectly from informants through interviews, observations, and documentation. Data analysis techniquesused are data reduction, data display, data verification, and affirmation of conclusions. An important findingin this study is that SD/MI Unggulan Ash-Shiddiqiyyah-3 di Purworejo cannot be said to be a quality school.Because, the three components of education quality have not been fulfilled, namely: overall input, process,and output.